2006
DOI: 10.1042/bst0341341
|View full text |Cite
|
Sign up to set email alerts
|

PPAR: a new pharmacological target for neuroprotection in stroke and neurodegenerative diseases

Abstract: PPARs (peroxisome-proliferator-activated receptors) are ligand-activated transcriptional factor receptors belonging to the so-called nuclear receptor family. The three isoforms of PPAR (alpha, beta/delta and gamma) are involved in regulation of lipid or glucose metabolism. Beyond metabolic effects, PPARalpha and PPARgamma activation also induces anti-inflammatory and antioxidant effects in different organs. These pleiotropic effects explain why PPARalpha or PPARgamma activation has been tested as a neuroprotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
171
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(180 citation statements)
references
References 44 publications
5
171
0
4
Order By: Relevance
“…Diabetic patients face an increased propensity to suffer a stroke, and stroke inflicts significantly more damage in diabetic and hypertensive patients than in normoglycemic and/or normotensive individuals (32,33,101). It was first observed that the PPAR-alpha and the PPAR-gamma agonists protect against stroke and that this beneficial outcome is associated with improved endothelial relaxation, reduced oxidative stress and decreased VCAM1 and ICAM1 expression (26,101,104). Several animal studies have demonstrated the beneficial effects of TZDs in improving post-ischemic functional outcome.…”
mentioning
confidence: 99%
“…Diabetic patients face an increased propensity to suffer a stroke, and stroke inflicts significantly more damage in diabetic and hypertensive patients than in normoglycemic and/or normotensive individuals (32,33,101). It was first observed that the PPAR-alpha and the PPAR-gamma agonists protect against stroke and that this beneficial outcome is associated with improved endothelial relaxation, reduced oxidative stress and decreased VCAM1 and ICAM1 expression (26,101,104). Several animal studies have demonstrated the beneficial effects of TZDs in improving post-ischemic functional outcome.…”
mentioning
confidence: 99%
“…The activation of PPARγ by T33 at the beginning of OGD did not lead to a higher level of activity of PPARγ after reperfusion, which could be attributed to mitigated stress by the treatment of T33. Moreover, previous studies have suggested that the activation of PPARγ promotes the repression of the exaggerated expression of inflammatory mediators that occurs in response to transient cerebral ischemia [12,38] . These actions of PPARγ could be mediated, at least in part, by inhibiting the I-κBα/NF-κB pathway, since I-κBα is a PPARγ target gene [39] .…”
Section: Discussionmentioning
confidence: 99%
“…Increased migration of Th2 lymphocytes across the BBB [79] and a possible role of Th2 mediators in neuroprotection and repair have recently been reported [80,81]. In addition to immunomodulatory activity of statins, lovastatin was also reported to induce the expression of PPAR-γ [82], whose activation is considered to be a pharmalogical target in neurodegenerative diseases [83]. These observations suggest that statin treatment may also provide neuroprotection by attenuation of inflammatory disease-induced glutamate/calcium-mediated demyelinative axonal damage in MS.…”
Section: Statins Inhibit Axonal Lossmentioning
confidence: 99%